DETERMINANTS OF INTEREST IN USING E-WALLETS IN TRANSACTIONS BETWEEN MUSLIM TRADERS AND CONSUMERS: FINANCIAL LITERACY, PERCEPTION OF EASE AND PERCEPTION OF RISK: (CASE STUDY IN THE TRADITIONAL MARKETS OF PEKALONGAN CITY) - Weni Novia Lestari; Mohammad Rosyada (Islamic Economic and Business Journal, 2026)
This study aims to analyze the influence of financial literacy, perceived ease of use, and perceived risk on the interest in using e-wallets in transactions between Muslim traders and consumers in traditional markets in Pekalongan City. This quantitative study used a questionnaire as a data collection instrument with a sample of 96 respondents taken using a purposive sampling technique. The collected data were then processed using Eviews. The results showed that financial literacy had a positive and significant influence on the interest in using e-wallets. However, perceived ease and perceived risk do not influence interest in using e-wallets. However, simultaneously, financial literacy, perceived ease of use, and perceived risk had a significant influence on the interest in using e-wallets